The characteristics and performance of sustainable-releasing compound carbon source material applied on groundwater nitrate in-situ remediation. (August 2018) - Zhang, Wen; Ruan, Xiaohong; Bai, Ying; Yin, Lin
Abstract: Recently, reductant and carbon source were frequently used in groundwater nitrate remediation worldwide. Agricultural waste as a promising organic carbon source, has been paid much attention but the problem of sustainability, bioavailability and secondary pollution remained unsolved. This study was conducted to depict the characteristic and performance of developed sustainable-releasing compound carbon source material (SCCM) applied on the in-situ remediation of nitrate in shallow groundwater. Results showed the SCCM based on agricultural waste and zero valent-iron (ZVI) has a stable carbon releasing rate, which is suitable for stimulating the low microbial active environment in groundwater continuously, and capable of avoiding rapid TOC releasing in the early stage. The released carbon sources in SCCM leachate were mainly small molecular alcohols and acids with high microbial availability. As in-situ permeable reactive barrier (PRB) filling material, SCCM can form an optimal carbon source radiation range of 20 cm, with a maximum efficient carbon source radius of 1 m, which can reach an extended active zone. A positive correlation between the ZVI content and nitrate removal rate was found. The chemical and microbiological evidence both indicated that the expected chemical reduction and biological denitrification was gradually established. Additionally, the absorption of ammonia and chroma by attapulgite effectively avoided the secondary pollution. In conclusion, the application of SCCM in groundwater nitrate in-situ remediation optimized the nitrate removal efficiency and provided theoretical basis for engineer carbon sources development from straw-type agricultural waste. Highlights: SCCM developed from agricultural waste could sustainably release biodegradable carbon and applied to groundwater nitrate in-situ remediation. SCCM remediation system can achieve a chemical-biological denitrification process and remove 70–90% nitrate with little secondary pollution. This study demonstrated a novel utilization of straw-type agricultural waste as PRB filling matrix for groundwater nitrate in-situ remediation.